Sarabande: «two-faced Janus» of the baroque repertoire - Zhukova, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. The study examines the evolution of the sarabande as a phenomenon that reflects the cultural dynamics of Early Modern Europe, focusing on its transformation from a popular Iberian dance, marked by rhythmic vitality and expressive corporeality, into a refined musical form associated with court etiquette and intellectual introspection. The relevance of the research lies in the need to reassess the sarabande not merely as a component of the Baroque suite, but as a genre shaped by social, theatrical, and ritual practices. The main objective of the study is to reveal the semantic and expressive duality of the sarabande and to trace the mechanisms of its stylistic transformation in instrumental music. The scientific novelty consists in identifying manifestations of medieval modal theory in the polyphony of Ukrainian partes, which affected the specificity and main features of partes art. Methodology integrates comparative historical analysis of literary and theoretical sources, examination of choreographic and musical treatises, and stylistic analysis of musical scores. This approach allows the research to correlate socio-cultural contexts with specific musical and performance practices. By comparing Spanish, French, and German traditions, the study demonstrates how the sarabande’s expressivity shifted from external gesture to internal emotional expression. Scientific novelty lies in highlighting the sarabande as a genre that simultaneously preserves and transforms its origins. The article shows how the sarabande maintained its inherent theatricality even when integrated into abstract instrumental forms, particularly in the works of French clavecinists (Louis Couperin, Jean-Henri d’Anglebert, François Couperin) and later in the sarabandes of Johann Sebastian Bach and George Frideric Handel, where ornamentation becomes a means of meditative expression. The main findings reveal the sarabande as a “double-faced” genre, oscillating between sensuality and solemnity, corporeality and reflection. The conclusion emphasizes the significance of the sarabande for art and education: it functions as a key interpretive model for historically informed performance, encourages reconsideration of ornamentation as a structural and expressive tool, and continues to inspire modern artistic practices, including cinema and neoclassical composition.